If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(3 + 4x) = 25 (3 * 4 + 4x * 4) = 25 (12 + 16x) = 25 Solving 12 + 16x = 25 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + 16x = 25 + -12 Combine like terms: 12 + -12 = 0 0 + 16x = 25 + -12 16x = 25 + -12 Combine like terms: 25 + -12 = 13 16x = 13 Divide each side by '16'. x = 0.8125 Simplifying x = 0.8125
| 4c-8=5c+15 | | (x-7)(x+3)=24 | | 10p-7=24 | | -11.4-m=10.9 | | 20p-7=24 | | 37+(9x-1)=90 | | 3x/4-2/3=5/6 | | (3y+7)(-4x+2)= | | (6x^2+7)-(-4y^2+7)= | | 6x+15=64 | | sinx=73 | | (x+1)(10x)=(12x+2)x | | (6x+36)=(2x-5) | | 30=-3(-6-2z) | | -9x-22=-184 | | 6w^4+w^3-3w^2=0 | | 56+(7x-1)=90 | | (15/8)=((17-x)/x) | | 5n(4n+1)=0 | | 16+5a=31 | | 10x-6/3-5x | | 32-66= | | x-34=5x+2 | | (2x+6)+(5x+6)= | | 2x(-33)= | | 3a+3-4a+8=6 | | X^2+22x=-20 | | 9=5p+15-4p | | r^2-r=21+3r | | 3-36= | | 8z^4+8z^3=z+1 | | -2y+9(-2y+1)=-5+7(-8-y) |